Single-nucleus transcriptomics reveals sepsis-related neurovascular dysfunction in the human hippocampus - Liu, Liu; Li, Pengfei; Wilkerson, Brent A.; Wu, Yan; Liu, Meng; Jiang, Wei; Hamlett, Eric D.; Carroll, Steven L.; Fan, Hongkuan (Frontiers in Immunology, 2025)
IntroductionSepsis is increasingly recognized as a major precipitant of long-term cognitive impairment, yet the cellular mechanisms underlying hippocampal vulnerability remain elusive.MethodsWe performed single-nucleus RNA sequencing of human hippocampal tissues from sepsis and control patients to profile neurovascular cell populations and their transcriptional changes.ResultsWe identified profound neurovascular alterations involving 21 distinct cell populations. Astrocytes and microglia exhibited marked polarization: Astrocyte 2 showed simultaneous upregulation of neurotoxic A1 and neuroprotective A2 gene signatures in sepsis, whereas Astrocyte 1 displayed reduced A1 activity and a relatively quiescent profile. Microglia 2 demonstrated a prominent M1-like inflammatory signature, including elevated HLA-DRA, IL1B, and TNF, while Microglia 1 downregulated both M1 and M2 markers, suggesting a hypo-responsive state. Intercellular communication analysis revealed intensified astrocyte–microglia interactions in the septic hippocampus. Endothelial and mural cells exhibited transcriptional signatures of blood-brain barrier disruption, oxidative stress, and compromised vascular homeostasis. Key molecular pathways associated with antigen presentation, cytokine signaling, and vascular permeability were selectively activated across neurovascular compartments.DiscussionThese findings uncover a coordinated glial and vascular response to systemic inflammation, driven in part by dysfunctional astrocyte–microglia crosstalk and pro-inflammatory polarization. Such changes may underlie blood-brain barrier breakdown and contribute to sustained neuroinflammation and cognitive decline in sepsis survivors. Targeting glial-vascular signaling axes and modulating astrocyte or microglial polarization states may offer promising avenues for therapeutic intervention in post-sepsis neurological sequelae.